The 1 μm wear particles entrainment in situ observation via fluorescent staining silica particles by silane coupling with Rhodamine B - Tokoroyama, T.; Okashita, M.; Fusetani, N.; Murashima, M.; Hashizume, N.; Tsuboi, R.; Shiomi, H.; Umehara, N. (Frontiers in Mechanical Engineering, 2024)
In this study, we conducted in-situ friction tests to investigate the entrainment of imitation wear particles at the contact point under boundary lubrication conditions. These imitation wear particles were glass beads with diameters of approximately 0.8 μm, 1.0 μm, and 3.0 μm, respectively. To address optical limitations, we stained these particles using silane coupling to attach Rhodamine B to the glass beads. We examined the effect of particle diameter on entrainment numbers under varying outside oil film thicknesses. The results showed that the entrainment number was highest when the outside oil film thickness matched the particle diameter. This clearly indicated that the outside oil film thickness significantly influenced the entrainment of particles.